2013
DOI: 10.5005/jp-journals-10024-1475
|View full text |Cite
|
Sign up to set email alerts
|

C-Arm Fluoroscopy: A Reliable Modality for Retrieval of Foreign Bodies in the Maxillofacial Region

Abstract: The anatomic complexity of the maxillofacial region makes the retrieval of foreign bodies a daunting task for the maxillofacial Surgeon. Moreover the inability of 2-dimensional imaging to precisely locate foreign bodies makes it challenging. The anatomic proximity of critical structures and esthetic considerations limits the access and thus poses a greater challenge for the surgeon in cases of foreign body retrieval. Hereby we propose a simple technique and a case report to support, the retrieval of small (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Additionally, fluoroscopy using a portable C-Arm x-ray imaging system was used with a metallic dissecting forceps as a radiographic reference (Figure 4). Several studies have reported the advantages of using fluoroscopy for intraoperative imaging of foreign bodies, as it enables anatomic visualization in multiple planes [5,[9][10][11][12]. In most of the above studies, a C-Arm x-ray system was the preferred method of fluoroscopic imaging, as was the case in the present study too.…”
Section: Table 1: List Of Cases Reporting Displacement To and Subsequ...supporting
confidence: 51%
See 2 more Smart Citations
“…Additionally, fluoroscopy using a portable C-Arm x-ray imaging system was used with a metallic dissecting forceps as a radiographic reference (Figure 4). Several studies have reported the advantages of using fluoroscopy for intraoperative imaging of foreign bodies, as it enables anatomic visualization in multiple planes [5,[9][10][11][12]. In most of the above studies, a C-Arm x-ray system was the preferred method of fluoroscopic imaging, as was the case in the present study too.…”
Section: Table 1: List Of Cases Reporting Displacement To and Subsequ...supporting
confidence: 51%
“…In scenarios wherein the foreign body displacement is witnessed clinically, imaging modalities play the role of the next important diagnostic tool. Plain radiographs and advanced imaging techniques such as ultrasonography, magnetic resonance imaging (MRI) and CT help localize the anatomic location of the foreign body and vital structures in its proximity [ 2 , 4 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential detect the exact location of FB for removal 2,4 . However, identifying the position of these objects and determining a safe surgical approach are difficult using conventional preoperative radiography 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It was first used in neurosurgery to improve the imaging of brain tumors, cysts, edema and diagnosis of central nervous system diseases 7 . The benefit exceeds surgery on the brain; fluoroscopy has been used a non -invasive method for guided surgical, due to the accuracy of location for removal of FB 4 . Also others reports demonstrate that fluoroscopy improves the management and resolution to removal of broken instruments and neddles in soft and hard tissue 3,8,9 .…”
Section: Introductionmentioning
confidence: 99%